Controllable in situ fabrication of self-lubricating nanocomposite coating for light alloys. (1st April 2022) - Yang, Zehui; Zhang, Zhen; Chen, Yongnan; Zhao, Qinyang; Xu, Yiku; Zhang, Fengying; Zhan, Haifei; Wang, Shaopeng; Li, Hongzhan; Hao, Jianmin; Zhao, Yongqing
Abstract: Intrinsic friction and corrosion issues of light alloys impede their application in tribological and corrosive environments, thus a proper ceramic coating is normally required to overcome these issues for practical engineering deployment. Here, we developed a new approach to fabricate controllable and self-lubricating nanocomposite coating by combining in-situ synthesis of MoS2 and plasma electrolytic oxidation (PEO) process. It is found that the coefficient of friction of this new coating is only about a quarter of the coatings obtained by traditional PEO process due to the self-lubricating characteristic of gradient MoS2 . More importantly, this ceramic coating exhibits excellent interfacial strengthen through edge-pinning by noncoherent, which endows excellent tribological and adhesive properties. This facile technique provides a new strategy to fabricate self-lubricating ceramic coating for light alloys, and is believed to have great potential applications in wide engineering sectors and open new avenues for designing novel alloy systems for extreme conditions. Graphical abstract: Image, graphical abstract